Effects of nicardipine on beating rates of cultured myocardial cells - YANG Jia-cui; YU Chuan-lin (Acta Pharmacologica Sinica, 2016)
Nicardipine (Nic) 15 nmol/L had no effects on beating rates of cultured myocardial cells. Nic 75 and 150 nmol/L depressed the beating rates significantly. Rapid standstills occurred earlier and more in 150 nmol/L group than in 75 nmol/L. Both isoproterenol and CaCl2 restored the beating depressed by Nic. However, only CaCl2 prevented the standstill. These results suggest that nicardipine may compete with calcium in excitation-contraction coupling.